The Effect of Grinding Conditions on Fine Galena Flotation and Separation from Pyrite - Yongjun Peng; Stephen Grano; Daniel Fornasiero; John Ralston (International Mineral Processing Congress, 2003)
"A specially designed mill which allowed the control of pH throughout grinding was used to study the effect of grinding conditions on galena flotation and galena separation from pyrite. The changes occurring on the mineral surface during grinding were investigated by EDTA extraction and ToF-SIMS measurements.Galena flotation and galena separation from pyrite were strongly dependent on the type and amount of oxidation species produced on galena and pyrite surfaces under different grinding conditions. Iron oxidation species depressed both galena and pyrite flotation, whilst lead oxidation species activated pyrite flotation but had little effect on galena flotation. Optimum galena flotation and galena selectivity against pyrite were achieved by selecting grinding conditions that enabled lead and iron oxidation production to be controlled.Grinding conditions had a large effect on the flotation of the galena particles of different sizes. Flotation of fine galena particles (-10 µm) was depressed by iron oxidation species derived from the grinding media. Chromium grinding medium decreased the production of iron oxidation species and therefore increased the flotation of fine galena particles."